Implementation of 3D Printing Technology into Primary and Secondary School Education Verified Methodology - Dosedla, Martin (Odborné a technické vzdělávání, 2023)
Title in English: Integrace technologie 3D tisku do výuky na základních a středních školách: Ověřená metodika With the development of 3D printing technology in recent years, there has been a significant decrease in the price of printers and thus an increase in the availability of this technology. This technological area opens up new possibilities in a wide range of fields from industry, medicine, construction and architecture to the level of everyday home use. We also see a huge didactic potential in 3D technology, which is currently not being used. The implementation of 3D technologies in teaching at primary and secondary schools enables the creation of completely new types of teaching aids and increases the availability of teaching models for pupils and students. Students can work with teaching models in class and, with methodological supports, they also actively participate in their creation.